Khoi asked in Science & MathematicsMathematics · 1 month ago

# 3x = x + 24 2x = 24 x = 12 Why 2x = 24?

Relevance
• Philip
Lv 6
1 month ago

3x = x+24;

Subtracting x from both sides gives  ;

2x = 24;

Division through by 2 gives;

x = 24. End of story.

• 1 month ago

3x=x+24  subtract x from both sides of the =

3x=x+24

-x=-x

----------------

2x=0+24 >>>2x=24

• 1 month ago

Why 2x = 24???

Remember you MUST keep the equals (=) in balance. Its like an old fashioned weigh scales.

Subtract 'x' from both sides; This is like taking weights of the same mass from a weigh balance scales.

Hence

3x - x = x - x + 24

3x take away an 'x' leaves '2x'

& 'x' take away an 'x' leaves no 'x'.

Hence

2x = 24

Keeping the weigh scales in balance, we divide both sides by '2'

2x/2 = 24/2

Cancel down by '2'

x = 12

Hope that helps!!!!

Remember ,where the 'equals' is concerned, whatever you do to one side, you MUST do to the other, other wise the 'equals/weigh scales' is  'unequal/unbalanced'.

• 1 month ago

3x=x+24

=>

3x-x=x+24-x

(reduce x from both sides; the balance is

still be kept)

=>

2x=24

(x is cancelled on the right side)

• David
Lv 7
1 month ago

If: 3x = x+24

Deduct x from both sides: 2x = 24

Divide both sides by 2: x = 12

• 1 month ago

3x = x + 24

3x - x = x - x + 24

2x = 24

• 1 month ago

If you start with an equation, you can do the same thing to both sides.  You can add the same thing, or subtract, or multiply, or divide. Except you can't divide by zero.

Subtract "x" from both sides.

3x minus x is 2x.

On the right side, x minus x is zero.

That gives us 2x = 0 + 24.

And 0 + 24 is the same as 24.

• Ash
Lv 7
1 month ago

3x = x + 24

We have to bring all x terms on one side and all  numbers on other

So we subtract x on both sides

3x - x = x + 24 - x

2x = 24

Now divide by 2 on both sides

2x/2 = 24/2

x = 12